SISTEM MONITORING SUHU DAN KELEMBAPAN BERBASIS IoT TERINTEGRASI APLIKASI MOBILE DI RUANG SERVER PTPN IV: IoT-BASED TEMPERATURE AND HUMIDITY MONITORING SYSTEM INTEGRATED WITH A MOBILE APPLICATION IN THE PTPN IV SERVER ROOM - Ahmad Billy Sutanto; Raden Aris Sugianto; Ritna Wahyuni; Andi Prayogi (LPPM Universitas Abdurrab, 2026)
A server room requires stable environmental conditions to maintain the performance of electronic devices, as excessive temperature and uncontrolled humidity can cause hardware damage. Manual monitoring implemented in the server room of PTPN IV Regional I still has limitations, such as delayed detection and the absence of digital data recording. This study aims to design and implement an Internet of Things (IoT)-based temperature and humidity monitoring system using a DHT22 sensor and ESP32 microcontroller. Data are transmitted in real-time to Firebase Realtime Database and displayed through a Flutter-based mobile application called ServGuard. The system is also equipped with remote Air Conditioner (AC) control features using an IR Transmitter. This research applied a quantitative approach through observation, direct measurement, and system testing. The results showed an average temperature reading difference of 0.23°C and humidity difference of 1.08% RH compared to standard measuring instruments. The alarm system was automatically activated when the temperature exceeded the predefined threshold, and all AC control commands were successfully executed. The ServGuard application and Firebase operated stably in real-time data synchronization. The developed system proved to be more effective than manual monitoring methods and has the potential for further development through artificial intelligence integration.